2003
DOI: 10.14712/18059694.2019.27
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Potential Toxic Effects After Repeated 10-Week Administration of a New Iron Chelator – Salicylaldehyde Isonicotinoyl Hydrazone (SIH) to Rabbits

Abstract: Salicylaldehyde Isonicotinoyl Hydrazone (SIH) – a Pyridoxal Isonicotinoyl Hydrazone (PIH) analogue – is an effective iron chelator with antioxidant and antimalarial effects, as documented in numerous in vitro studies. However, no toxicological data obtained from in vivo studies have been made available yet. In this study, the potential toxic effects of repeated administration of SIH (50 mg/kg, once weekly, 10 weeks, i.p.), partially dissolved in a 10 % Cremophor solution, on various biochemical, haematological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…SIH is a highly lipophilic chelator and as a result has increased cell permeability. A number of studies have demonstrated that SIH may have a role in mitigating oxidative-stress induced damage to cardiomyocytes[146-148]. In our studies, SIH protects cultured RPE cells against hydrogen peroxide toxicity [149].…”
Section: Potential Therapiessupporting
confidence: 50%
“…SIH is a highly lipophilic chelator and as a result has increased cell permeability. A number of studies have demonstrated that SIH may have a role in mitigating oxidative-stress induced damage to cardiomyocytes[146-148]. In our studies, SIH protects cultured RPE cells against hydrogen peroxide toxicity [149].…”
Section: Potential Therapiessupporting
confidence: 50%
“…Indeed, SIH has previously shown the best “therapeutic” ratio of inherent toxicity and cytoprotective efficiency against diverse ROS-mediated injuries (H 2 O 2 , tert -butyl hydroperoxide, catecholamines and their oxidation products) when compared with other Fe chelators, including the clinically-approved agents DFO, ICL670A or L1 [16, 17]. Of note, SIH has a very favorable in vivo toxicological profile, as it was well tolerated and induced no histopathological signs of organ toxicity or changes of biochemical and hematological parameters following its 10-week repeated administration to rabbits [51]. …”
Section: Discussionmentioning
confidence: 99%
“…Marked protective potential of SIH has been also shown in anthracycline cardiotoxicity both in vitro using neonatal cardiomyocytes [9] and in vivo in a chronic model of daunorubicin-induced heart failure in rabbits [10]. Importantly, good inherent tolerability and low toxicity profile of SIH have been demonstrated following its 10-weeks repeated administration to rabbits [11]. …”
Section: Introductionmentioning
confidence: 99%